ANALYSIS OF FACTORS CAUSING KEK (CHRONIC ENERGY DEFICIENCY) IN PREGNANT WOMEN AT PUSKESMAS DARUL FALAH, EAST ACEH DISTRICT IN 2024 - Damanik, Lisa Putri Utami; Marlina, Lenny; Adethia, Kismiasih; Pitaloka, Diah; Tobing, Nadia Elsani L; Sembiring, Mediana Br (Yayasan Nuraini Ibrahim Mandiri, 2024)
This study aims to analyse the factors that cause Chronic Energy Deficiency (CHD) in pregnant women at Darul Falah Health Centre, East Aceh District, in 2024. SEZ in pregnant women is one of the nutritional problems that can cause serious complications, both for the mother and the fetus she is carrying, such as low birth weight babies (LBW), anaemia, and the risk of difficult childbirth. This study used an analytical survey method with a case control approach on 66 respondents selected proportionally with random sampling technique. Data were collected through questionnaires and analysed using the chi-square test. The results showed that maternal age, anaemia, and emesis gravidarum had a significant association with the incidence of SEZ in pregnant women (p < 0.05), while the gestational age factor did not show a significant association. Anaemia and emesis gravidarum were the most influential factors for the incidence of SEZ, with a risk of 17.5 times and 10.07 times greater respectively than pregnant women who did not experience these conditions. This study confirms the importance of regular health monitoring of pregnant women, nutrition education, and intervention in the form of supplementary feeding to prevent the occurrence of SEZ and its complications. Keywords: Chronic Energy Deficiency, Pregnant Women, Anaemia, Emesis Gravidarum